FORMULATION AND EVALUATION OF ORODISPERSIBLE TABLETS OF LAMOTRIGINEUSING DISCRETE SUPER DISINTEGRANTS AND COPROCESSED EXCIPIENTS - POONURU, RAJASEKHAR; CHERUKU, ROHINI; JULURI, PAVAN; JABEEN, KHADEERA; SREERAMULA, SWETHA; BANDARI, SNEHA; MADUPU, AKHILA (International Journal of Pharmacy and Pharmaceutical Sciences, 2020)
Objective: The present study was designed to formulate and evaluate the orodispersible tablets of lamotrigine after enhancing its solubility. Methods: Lamotrigine was made into an inclusion complex with eudragit E 100 my kneading and mass extrusion method and later this mixture is compressed into orodispersible tablet using various super disintegrants and co-processed excipients to reduce the disintegration time for providing prompt action through rapid drug release. Results: Lamotrigine ODTs containing F-melt (F1-3%, F2-5%) dispersed in lesser time of (9±0.11) and (21±0.58) compared to formulations with polyplasdone XL-10 and primellose as super disintegrants respectively with F1 showing short wetting time. The water absorption was also was found to be more for formulation with 3% F-Melt. Conclusion: Lamotrigine orodispersible tablets were prepared by direct compression technique by using 3% and 5% of three super disintegrants (f-melt, primellose and polyplasdone XL-10). Disintegration time of F1 (3% f-melt) formulation was found to be least (7 sec).